Increasing Student Motivation in Completing School Assignments Through Information Services - Rajab, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
This research aims to describe the condition of students' motivation in completing assignments before and after being given information services and identify the level of differences. This research uses a quantitative method with a quasi-experimental approach of The type One-Group Pre-Test Post-Test Design . Data analysis was carried out by different tests using the Wilcoxon signed ranks test technique with the help of SPSS version 20.0. The research findings showed that there were significant differences in students' motivation in completing assignments before (average score = 161.9 ) and after (average score = 179.3) participating in information services. This means that there is an increase in the average student motivation score so that it can be concluded that the provision of information services can increase student motivation in completing assignments.